Model for Development of Teaching Materials for Lecture on Tax Accounting with Computer Tax Program - Jasman Saripuddin S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
One of the objectives of the preparation of the Tax Report is to provide information to parties who need it that will be used to make comparisons, assess the ability of a company, and as a guide for decision-making.